2005
DOI: 10.1038/sj.bjc.6602822
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 immunodetection in follicular thyroid neoplasms: a prospective study on fine-needle aspiration samples

Abstract: Fine-needle aspiration cytology, which is well established to be accurate for the diagnosis of thyroid cancer, may be inconclusive for the follicular thyroid neoplasms. As galectin-3 was suggested to be a marker of malignant thyrocytes, we investigated whether this protein might be helpful in the diagnosis of aspirates classified as undeterminate by cytology. After establishing an easy processing of aspirates for galectin-3 immunodetection, a series of aspirates categorised as benign (n ¼ 63), malignant (n ¼ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 30 publications
1
38
2
Order By: Relevance
“…However, data from us and other laboratories show that galectin-3 test method works well also in follicular carcinomas (Bartolazzi et al, 2001;Oestreicher-Kedem et al, 2004;Collet et al, 2005;Papotti et al, 2005;Saggiorato et al, 2005). By the practical point of view, the incidence of well-differentiated follicular carcinomas is low (less than 10% of the cases) and is markedly reduced in countries without iodine deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data from us and other laboratories show that galectin-3 test method works well also in follicular carcinomas (Bartolazzi et al, 2001;Oestreicher-Kedem et al, 2004;Collet et al, 2005;Papotti et al, 2005;Saggiorato et al, 2005). By the practical point of view, the incidence of well-differentiated follicular carcinomas is low (less than 10% of the cases) and is markedly reduced in countries without iodine deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We and other laboratories have recently proposed the use of galectin-3 expression analysis for the preoperative characterisation of follicular thyroid nodules (Orlandi et al, 1998;Gasbarri et al, 1999;Inohara et al, 1999;Bartolazzi et al, 2001;Herrmann et al, 2002;Collet et al, 2005). Although many reports have been published on this issue during the last decade (about 100 papers are displayed in Pub Med since 1997) some authors experienced conflicting results with the use of galectin-3 for improving diagnosis of follicular thyroid proliferations (Martins et al, 2002;Niedziela et al, 2002;Feilchenfeldt et al, 2003;JakubiakWielganowicz et al, 2003;De-Leon-Mazariegos et al, 2004;Mehrotra et al, 2004;Mills et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of false positive cases was also noticed by Collet et al [60], they suggested that these benign lesions (MNG and adenomas) present foci of clonal expansion, suggesting a stage in the multistep evolution of goiters and adenomas to carcinoma, and they concluded that, adenomas with positive expression for galectin-3 could be considered potential early cancer, and hence require therapeutic surgical intervention.. The same recommendations were also made by Saggirato et al [14] and Bartolazzi et al [15] and Lubiz et al [29] they also suggested that a new possibility of early detection of thyroid cancer can be accomplished by Galectin-3 immunostaining method, and they recommended further work to ensure the accuracy of this suggestion.…”
Section: Galectin-3 X 400) 2-b: Follicular Carcinoma Showing Diffusementioning
confidence: 59%
“…In several studies, the immunoexpression of Galectin-3 was stated as a highly sensitive and specific marker for the thyroid carcinomas with follicular origin, particularly for papillary thyroid carcinomas (17)(18)(19)(20)(21)(22)30).…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 allows clinicians to identify the subgroup of the patients with a suspicious lesion but a low risk of malignancy, for whom a careful follow-up would be more appropriate rather than surgery (19). To avoid unnecessary aggressive surgery, Galectin-3 is recommended for the histological diagnosis of follicular lesions and for preoperative evaluation of the lesions with indeterminate thyroid cytology (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%